Sistem Pendukung Keputusan Penentu Ancaman Pidana Menggunakan Metode Technique For Order Performance of Similarity (TOPSIS) - Muh. Surya Alda Akbar. S (Lembaga Pengembangan Kinerja Dosen, 2024)
In this era of increasingly advanced technology, all groups can easily use the Internet. This convenience is also experienced by children who access the internet and imitate contemporary things. The lack of filters for children when accessing the internet causes children to imitate bad things. This is what causes bad behavior and tends to lead to crime. Violators will be punished according to the 1945 Constitution. Indonesia is a country that upholds the law. The results of the Third Amendment stipulate that every aspect of social, state and government life must always be based on law. Therefore, individuals may be subject to fines according to applicable regulations. The trial lasted so long that the public did not know how the trial was going. Defendants arrested in criminal cases also face very lengthy trial processes. Therefore, a decision support system was built to determine the threat of punishment for criminals using the TOPSIS (Technique for Order Performance of Similarity) method. This system aims to speed up the decision-making process and become more efficient over time. This method will make decisions based on the weight values ​​determined by domain experts.